Public universities and regional growth : insights from the University of California - Kenney, Martin; Mowery, David C. (Innovation and technology in the world economy., 2014)
Public Universities and Regional Growth examines evolutions in research and innovation at six University of California campuses. Each chapter presents a deep, historical analysis that traces the dynamic interaction between particular campuses and regional firms in industries that range from biotechnology, scientific instruments, and semiconductors, to software, wine, and wireless technologies. The book provides a uniquely comprehensive and cohesive look at the University of California's complex relationships with regional entrepreneurs. As a leading public institution, the UC is an examplar for.